Demethylation of MicroRNA-124a Genes Attenuated Proliferation of Rheumatoid Arthritis Derived Fibroblast-Like Synoviocytes and Synthesis of Tumor Necrosis Factor-α. - Qiao Zhou; Li Long; Ting Zhou; Juan Tian; Bin Zhou (PLoS ONE, 2016)
Objective To examine the impact of 5-Aza-2'-deoxycytidine (5-AzadC) on methylation status of miR-124a genes in rheumatoid arthritis (RA) associated fibroblast-like synoviocytes (FLS) and its effect on RA-FLS proliferation and TNF-α expression. Materials and methods FLS were isolated from seven RA-derived synovial tissues and cultured in vitro. The expression of miR-124a was measured by real time quantitative polymerase chain reaction (PCR) in FLS with or without 5-AzadC treatment. MiR-124a gene methylation was detected by methylation-specific PCR. FLS were divided into three groups as control, IL-1β and IL-1β/5-AzadC, respectively. The cells in the IL-1β group were treated with 5 μg/L of IL-1β for 24 hours, whereas the cells in the IL-1β/5-AzadC group were first treated with IL-1β exactly as those in the IL-1β group for 24 h but further treated with 1μM 5-AzadC for additional 3 days. The cell growth was estimated based on absorbance at UV450nm. Secreted TNF-α from the cells was evaluated by enzyme-linked immunosorbent assay. After that, RA-FLS treated with IL-1β plus 5-AzadC were further transfected with miR-124a inhibitor or scrambled control. After culturing for 3 days, cell growth and TNF-α concentrations were measured. Results After 5-AzadC treatment, the expression of miR-124a was significantly increased compared with the control group (1.545 ± 0.189 vs 0.836 ± 0.166, p = 0.001). On the other hand, 5-AzadC significantly reduced IL-1β-mediated cell proliferation by nearly 2.5 fold (p = 0.006). Also, the level of TNF-α secreted from the cells treated with IL-1β plus 5-AzadC was considerably less than that from the cells treated with IL-1β alone (324.99 ± 22.73 ng/L vs 387.91 ± 58.51 ng/L, p = 0.022). After transfection with miR-124a inhibitor in RA-FLS treated with IL-1β plus 5-AzadC, the cell proliferation was increased by 18.2% and the TNF-α expression was increased by 19.0% (p = 0.001 and 0.011, respectively). Conclusion Methylation of miR-124a genes contributed to IL-1β-mediated RA-FLS proliferation and TNF-α expression.